2018
DOI: 10.1002/cam4.1734
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation of radiotherapy in unresectable extrahepatic cholangiocarcinoma

Abstract: PurposeTo evaluate the effect of escalated dose radiation therapy (EDR, defined as doses >50.4 Gy in 28 fractions [59.5 Gy BED]) on overall survival (OS), freedom from local progression (FFLP), and freedom from distant progression (FFDP) of patients with unresectable extrahepatic cholangiocarcinoma (EHCC).MethodsA consecutive cohort of 80 patients who underwent radiotherapy for unresectable EHCC from 2001 to 2015 was identified. Demographic, tumor, treatment, toxicity, and laboratory variables were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 31 publications
(50 reference statements)
4
42
5
Order By: Relevance
“…The most frequent sites of local recurrence were the hepatectomy stump, the anastomosis, or both. Several reports that determined the sites of local recurrence with or without adjuvant chemotherapy found that the most common are biliary anastomosis, the liver incision, and choledochojejunostomy, with recurrence rates ranging from 36.4-59% [1,30,31]. Thus, the frequencies of local recurrence sites are similar with or without RT; however, our present data indicate that the recurrence rates were lower for patients administered adjuvant RT.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The most frequent sites of local recurrence were the hepatectomy stump, the anastomosis, or both. Several reports that determined the sites of local recurrence with or without adjuvant chemotherapy found that the most common are biliary anastomosis, the liver incision, and choledochojejunostomy, with recurrence rates ranging from 36.4-59% [1,30,31]. Thus, the frequencies of local recurrence sites are similar with or without RT; however, our present data indicate that the recurrence rates were lower for patients administered adjuvant RT.…”
Section: Discussionsupporting
confidence: 51%
“…Age is a prognostic factor for CCA [1]. Moreover, some studies show that tumor size and multiple tumors (satellite tumor) are prognostic factors of CCA [1,30,31]. In the present study, there was no signi cant difference in tumor size (data not shown), and patients did not have detectable satellite tumors.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The regimen of gemcitabine and cisplatin was recommended for inoperable or postoperative pCCA patients [4,37], but detailed chemotherapy regimen information were unavailable in SEER database. Patients with extrahepatic cholangiocarcinoma may be offered chemoradiation therapy, which was administered with a dose of 45 Gy to regional lymphatics and 54 to 59.4 Gy to the tumor bed [38,39]. With respect to the radiotherapy for perihilar cholangiocarcinoma, Leng et al [40] argued that adjuvant radiotherapy was of no association with survival improvement for resected pCCA groups.…”
Section: Discussionmentioning
confidence: 99%